PEMBELAJARAN SEJARAH MELALUI AUDIO VISUAL DAN BISINDO BAGI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH SLB NEGERI KARANGANYAR - Alam, Muhammad Bagus Sekar; Warto, Warto; Yulianti, Umi; Hastuti, Tiwuk Kusuma; Setiasih, Insiwi Febriary; Wardojo, Waskito Widi; Juwono, Harto (Universitas Mataram, 2024)
This Community Service Activity will help students with Special Needs in the process of learning history by presenting materials in the form of audio visuals equipped with sign language translation facilities (Bisindo). This is strengthened by the support of the Indonesian government through Law No. 8 of 2016 concerning the policy of educational services for Children with Special Needs (ABK). Community service activities that present learning media are expected to make it easier for students to understand the correct material. The partners of this service are students of Karanganyar State Special Needs High School. This community service aims to make it easier for students with special needs to understand Indonesian historical events, as well as help raise awareness of Indonesian history and be able to understand the meaning of the historical events being studied. In the implementation of community service activities, observation, discussion, and direct assistance methods are used. While in the process of making historical videos, historical methods are used including Topic Selection, Heuristics, Interpretation, Historiography, and continued with video digitization. This community service activity will do several things, including discussions with teachers about determining historical material, collecting sources, criticizing sources, and historiography stages. The activity continues with the process of compiling video scripts, compiling videos, editing and launching videos. All activities are carried out in stages by involving teachers and school administrators. The output of the community service activities is that students understand historical events with interesting and enjoyable presentation of materials, Indonesian history videos equipped with sign language translation facilities (BISINDO). In addition, the creation of activity videos, promotional media through print and online media, and scientific publications in the Nationally accredited journal Sinta 3. It can be concluded that this community service activity provides the desired benefits. Proven by the existence of a questionnaire regarding the material in the video, students are able to answer correctly.